Prolapse and amputation of phallus in a greater rhea (Rhea americana) kept in captivity: Case report (Research, Society and Development, 2022)
Rheas are the largest birds in South America. Belonging to the order of Struthioniformes, they are bred in captivity for their beauty and also for the quality and use of their meat, leather, feathers and eggs. The objective of this report was to describe a case of prolapse and amputation of the phallus after clinical and surgical care of a greater rhea (Rhea americana), to contribute to the literature on the occurrence of this condition in ratites. The animal was raised and is kept in captivity at Federal University of Piauí (UFPI), in Teresina, Piaui state, Brazil. The animal relapsed after two attempts to reduce the phallus prolapse, requiring amputation, since the animal’s organ presented areas of necrosis. After the intervention, the animal was returned to the previous enclosure, regrouping with the flock without complications and maintained a normal pre-surgery behavior.  To the author’s knowledge, this is the first case of phallus and cloaca prolapse reported in Rhea americana.